2018
DOI: 10.1002/jcb.27882
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR‐146b‐5p promotes T cell acute lymphoblastic leukemia migration and invasion via the IL‐17A pathway

Abstract: Metastatic disease remains the primary cause of death for individuals with T cell acute lymphoblastic leukemia (T‐ALL). microRNAs (miRNAs) play important roles in the pathogenesis of T‐ALL by inhibiting gene expression at posttranscriptional levels. The goal of the current project is to identify any significant miRNAs in T‐ALL metastasis. We observed miR‐146b‐5p to be downregulated in T‐ALL patients and cell lines, and bioinformatics analysis implicated miR‐146b‐5p in the hematopoietic system. miR‐146b‐5p inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…32 Similarly, Tu et al found that loss of miR-146b-5p up-regulated MMP-9 expression via the NF-κB signalling pathway, to promote T-ALL cell migration and invasion. 6 Very importantly, previous evidence also highlighted that IRAK-1 could lead to the activation of NF-κB. 33 In conclusion, our study elucidated the possible pathway that DNA methylation at the promotor region causes miR-204 silencing,…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…32 Similarly, Tu et al found that loss of miR-146b-5p up-regulated MMP-9 expression via the NF-κB signalling pathway, to promote T-ALL cell migration and invasion. 6 Very importantly, previous evidence also highlighted that IRAK-1 could lead to the activation of NF-κB. 33 In conclusion, our study elucidated the possible pathway that DNA methylation at the promotor region causes miR-204 silencing,…”
Section: Discussionmentioning
confidence: 55%
“…inhibitor-NC, (4) inhibitor-miR-204, (5) mimic-NC + oe-NC, (6) mimic-miR-204 + oe-NC, (7) mimic-miR-204 + oe-IRAK1, (8) mimic-NC + oe-NC, (9) mimic-miR-204 + oe-NC, (10) mimic-miR-204 + oe-p65, (11) oe-NC + si-NC, (12) oe-IRAK1 + si-NC or (13) oe-IRAK1 + si-p65.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Downregulation of miR‐146b in T cell ALL has been reported. A study by Tu et al demonstrated that loss of miR‐146b contributes to the promotion of metastasis through the IL7A pathway. Mechanistically, MMP‐9 is a potential effector of IL7A, and IL7A is a target gene for miR‐146b.…”
Section: Mirna Associated With Emt In Allmentioning
confidence: 99%
“…Mechanistically, MMP‐9 is a potential effector of IL7A, and IL7A is a target gene for miR‐146b. Therefore, miR‐146b acts as a tumour suppressor miRNA in T cell ALL, and downregulation of miR‐146b is associated with poor prognosis and the promotion of metastasis in T cell ALL …”
Section: Mirna Associated With Emt In Allmentioning
confidence: 99%
“…Accumulating studies have revealed that miRNAs are widely distributed in animals, plants and certain viruses, and they have been determined to be key regulators of numerous important biological processes, including cell proliferation, differentiation and inflammation (9)(10)(11). As one of the commonly investigated miRNAs, miR-146b has been implicated in the malignant proliferation of various cancer cell types (including ovarian and papillary thyroid cancer cells) and several immune activities, including innate immune sensing and pro-inflammatory cytokine release (12)(13)(14)(15)(16). Several studies have revealed that miR-146b expression is increased in several autoimmune diseases [including rheumatoid arthritis (RA), multiple sclerosis and autoimmune thyroid diseases (ATD)] (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%